CONSTRUCTING RUBRICS FOR GENRES AND SHORT FUNCTIONAL TEXTS: (A New Challenging Task for English Language Teachers) - Azhar, Fadly (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractTo enable the students of junior and senior high schools in Indonesia to write such short functional texts as announcement, message, advertisement, brochure, and letters; and such genres as narrative, recount, news item, report, descriptive, explanation, procedure, analytical exposition, hortatory exposition, discussion, is the main target of the teaching of writing skill (Curriculum 2004, 2006, and 2013). To reach this target, of course, teachers should teach all theoretical concepts related to these kinds of texts and ask students to write. However, teachers prefer to give only the examples of each short functional texts and genres; and in the real classroom evaluation, students are required to answer a multiple-choice question that is similar to reading comprehension. This condition also happens in the school-leaving exams and national exam. Consequently, students got difficulties to write a grammatical and well-organized genres as well as short functional texts; even the teachers will have no experiences at all on how to construct a fit, proper, and feasible rubric for those texts. This is due to fact that more than 50% of new students (i.e. freshmen) of English Department Faculty of Education and Teacher Training University of Riau Pekanbaru have moderate to low levels ability in writing skill, particularly in terms of genres, short functional texts including essays or projects (Results of Writing Course I, Academic Year 2014/2015). In relation to this, about most English teachers of Province of Riau attending Education & Training of Certification (18-27 October 2015) said that they had difficulties to construct rubrics for a specific short functional text. This paper will try to disclose how to construct and apply rubrics for those texts that will be a new challenging task for English language teachers within Riau Province and Indonesia.Key words: constructing, rubrics, genres, short functional texts